Measuring the Financial Performance of Enterprises Under Ministry of Energy and Mineral Resources (EMR) an Indonesia Experience - Mardawiyah Daryanto, Wiwiek; Samidi, Sudarmawan (International Journal of Engineering and Technology, 2018)
The assessment of financial performance is becoming increasingly important. The Decree No. KEP-100/MBU/2002 issued by Ministry of Stated Owned Enterprises of Indonesia on June 2002 provide the mandatory measuring and rating the financial health condition for all subsidiaries of SOEs. The circumstance is of relevance in the Indonesian context, characterized by a strong corporate governance but the lack of transparency. This study aims to measure the level of financial performance by investigating return on equity, return on investment, cash ratio, current ratio, collection period, inventory turnover, total asset turnover and total equity to total asset ratio. Then, to compare the companyâ€™s financial performance between coal mining and natural gas industry. The data were collected from two stated owned enterprises under Ministry of Energy and Mineral Resources (EMR) for the period 2011 â€“ 2015. The result shows that the industry has a good financial health condition which achieved level AAA and AA. Furthermore, this industry has a challenge in inventory management and assets utilization. Therefore, this study can be useful for the manager to tackle the challenge and improve its efficiency.Â Â